Navigating oxygen deprivation: liver transcriptomic responses of the red eared slider turtle to environmental anoxia - Biggar,Kyle K.; Zhang,Jing; Storey,Kenneth B. (PeerJ, 2019)
The best facultative anaerobes among vertebrates are members of the genera Trachemys (pond slider turtles) and Chrysemys (painted turtles), and are able to survive without oxygen for up to 12 to 18 weeks at ∼3 °C. In this study, we utilized RNAseq to profile the transcriptomic changes that take place in response to 20 hrs of anoxia at 5 °C in the liver of the red eared slide turtle (Trachemys scripta elegans). Sequencing reads were obtained from at least 18,169 different genes and represented a minimum 49x coverage of the C. picta bellii exome. A total of 3,105 genes showed statistically significant changes in gene expression between the two animal groups, of which 971 also exhibited a fold change equal to or greater than 50% of control normoxic values. This study also highlights a number of anoxia-responsive molecular pathways that are may be important to navigating anoxia survival. These pathways were enriched in mRNA found to significantly increase in response to anoxia and included molecular processes such as DNA damage repair and metabolic reprogramming. For example, our results indicate that the anoxic turtle may utilize succinate metabolism to yield a molecule of GTP in addition to the two molecules that results from lactate production, and agrees with other established models of anoxia tolerance. Collectively, our analysis provides a snapshot of the molecular landscape of the anoxic turtle and may provide hints into the how this animal is capable of surviving this extreme environmental stress.
Keywords: Anoxia tolerance; Hypometabolism; Metabolic rate depression; Red eared slider turtle; DNA damage response